Intramolecular direct arylation - Corrie, Thomas James Alexander (The University of Edinburgh, 2017)
The research conducted for this thesis has led to the development of an intramolecular gold-catalysed direct arylation protocol whereby tethered arenes and aryltrimethylsilanes are coupled (Scheme 1). In Chapter 1, the key synthetic and mechanistic studies that have ultimately led to the conception of this project are introduced. In Chapter 2, the substrate scope of intramolecular direct arylation is assessed. The reaction tolerates a wide range of substrates with tether lengths between one and five units (containing C, N and O) generating 5- to 9- membered rings. Substrates that lead to 5-membered rings (1 → 2) can tolerate a broad electronic range of substituents and proceed under the mildest reaction conditions (≤ 1 mol% catalyst, room temperature) and with excellent yields. A smaller collection of examples is demonstrated for the cyclisation to 6- and 7- membered rings (3 → 4, 5 → 6), but no heating is required and good yields are maintained throughout the series. The synthetically challenging synthesis of 8- and 9- membered rings (7 → 8, 9 → 10) is successful, albeit with slightly more forcing conditions (4 mol%, up to 50 °C). The methodology was subsequently applied in the successful 10-step synthesis of natural product allocolchicine 11. In Chapter 3, the operative reaction mechanism is elucidated. Reaction monitoring techniques allowed for the detailed study of linear free energy relationships (LFERs) and kinetic isotope effects (KIEs), which in turn allowed for deduction of the reaction turnover-limiting step (TLS) and thus the first quantitative experimental data on the effects of aryl electron demand and conformational freedom on the rate of reductive elimination from diarylgold(III) species. The mechanistic investigation led to the observation of complex kinetic profiles for specific substrates. The origin of these unusual effects is the focus of Chapter 4. By combining experiment with kinetic simulation, an off-cycle catalyst inhibition pathway was identified and the understanding of this process allowed for a re-optimisation of reaction conditions. In Chapter 5, the general kinetic parameters that could govern any domino reaction combining inter- and intramolecular direct arylation are deduced through kinetic analysis and simulation of hypothetical systems. The results of the kinetic analysis were proved experimentally through the successful combination of intra- and intermolecular gold-catalysed direct arylation. The products of intramolecular cyclisation 2, generated in-situ, are demonstrated to couple with intermolecular aryltrimethylsilanes 12, resulting in a rapid increase in molecular complexity from simple substrates in one pot.
Keywords: gold-catalysis; cross-coupling; intermolecular reaction; tethered arenes; aryltrimethylsilanes